2015
DOI: 10.1002/elan.201400672
|View full text |Cite
|
Sign up to set email alerts
|

A Novel DNA Probe Based on Molecularly Imprinted Polymer Modified Electrode for the Electrochemical Monitoring of DNA

Abstract: A DNA probe that was based on methylene blue (MB) imprinted polyvinyl pyridine polymer (MIP) modified carbon paste electrodes were developed for the first time for electrochemical monitoring of DNA. Probes were built up by adsorbing MB onto modified electrodes prior to DNA immobilization. It was shown that DNA strongly immobilizes on MIP modified electrodes when MB was adsorbed in advance of DNA immobilization. The performance of the MB imprinted polymer modified carbon paste electrodes (MIP‐CPE) to rebind the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A molecularly imprinted electrochemoluminescence sensor for ultrasensitive HIV-1 gene detection using EuS nanocrystals as luminophore was developed [ 190 ]. Methylene blue imprinted polyvinyl pyridine polymer modified carbon paste electrodes were applied for the electrochemical monitoring of DNA [ 196 ].…”
Section: Formation Of Mips Imprinted By Proteins and By Other Largmentioning
confidence: 99%
“…A molecularly imprinted electrochemoluminescence sensor for ultrasensitive HIV-1 gene detection using EuS nanocrystals as luminophore was developed [ 190 ]. Methylene blue imprinted polyvinyl pyridine polymer modified carbon paste electrodes were applied for the electrochemical monitoring of DNA [ 196 ].…”
Section: Formation Of Mips Imprinted By Proteins and By Other Largmentioning
confidence: 99%
“…MIP-formation is a highly multidisciplinary approach, which involves polymer and organic chemistry and nanotechnology [ 169 , 170 ]. It should be noted that DNA [ 27 ] can also be entrapped [ 24 ] or molecularly imprinted [ 171 , 172 , 173 ] within conducting polymers and applied for bioanalytical purposes. Therefore, a lot of researchers are targeted towards the replacement of biomolecules, such as receptors, antibodies, DNA-based sequences and DNA-aptamers, with molecularly imprinted polymer-based structures or by artificial receptors [ 174 ].…”
Section: Mips Structures Imprinted By Biomolecules Of High Molecular ...mentioning
confidence: 99%
“…MIP-formation needs knowledge in organic and polymer chemistry [160,161]. It was demonstrated that DNA [29] can be entrapped [26] and molecularly imprinted [162][163][164] within CP-based layers. Therefore, some investigations are dedicated to replace direct application of DNA-based sequences in analytical systems [165].…”
Section: Polymers Imprinted By Proteins and Large Biological Compoundsmentioning
confidence: 99%